Structural and Functional Basis of Plasminogen Activation by Staphylokinase - Jespers, L.; Vanwetswinkel, S.; Lijnen, H. R.; Van Herzeele, N.; Van Hoef, B.; Demarsin, E.; Collen, D.; De Maeyer, M. (Thrombosis and Haemostasis, 1999)
Staphylokinase (Sak), a 15.5-kDa bacterial protein, forms a complex with human plasmin, which in turn activates other plasminogen molecules to plasmin. Three recombinant DNA-based approaches, (i) site directed substitution with alanine, (ii) search for proximity relationships at the complex interface, and (iii) active-site accessibility to protease inhibitors have been used to deduce a coherent docking model of the crystal structure of Sak on the homology-based model of micro-plasmin (μPli), the serine protease domain of plasmin. Sak binding on μPli is primarily mediated by two surface-exposed loops, loops 174 and 215, at the rim of the active-site cleft, while the binding epitope of Sak on μPli involves several residues located in the flexible NH2-terminal arm and in the five-stranded mixed β-sheet. Several Sak residues located within the unique μ-helix and the β2 strand do not contribute to the binding epitope but are essential to induce plasminogen activating potential in the Sak:μPli complex. These residues form a topologically distinct activation epitope, which, upon binding of Sak to the catalytic domain of μPli, protrudes into a broad groove near the catalytic triad of μPli, thereby generating a competent binding pocket for micro-plasminogen (μPlg), which buries approximately 2500 Å of the Sak:μPli complex upon binding. This structural and functional model may serve as a template for the design of improved Sak-derived thrombolytic agents. Following the completion and presentation of the present study, the deduced Sak:μPli:μPlg complex was fully confirmed by X-ray crystallography, which further illustrates the power and potential of the present approach.